2021
DOI: 10.3389/fsurg.2021.714950
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Submucosal With Intramuscular or Intravenous Administration of Dexamethasone for Third Molar Surgeries: A Systematic Review and Meta-Analysis

Abstract: Objective: The study aimed to review evidence on the efficacy of submucosal (SM) administration vs. intravenous (IV) or intramuscular (IM) route of injections of dexamethasone for improving outcomes after mandibular third molar surgery.Methods: PubMed, Embase, CENTRAL, and Google Scholar were searched for randomized controlled trials (RCTs) up to 20th May 2021. Early (2–3 days) and late (7 days) outcomes were compared between SM vs. IV or IM dexamethasone. Quality of evidence was assessed based on GRADE.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Brković et al [ 18 ] found that ropivacaine as supplemental injection provides a longer duration of postoperative analgesia, compared to placebo. Sub-mucosal dexamethasone injection had a significant beneficial postoperative effect on pain and trismus on the operating site [ 19 ], although there was no difference in late pain between the sub-mucosal, intravenous or intramuscular routes of administration [ 20 ]. Installation of a collagen sponge in the alveoli statistically significantly reduced pain [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brković et al [ 18 ] found that ropivacaine as supplemental injection provides a longer duration of postoperative analgesia, compared to placebo. Sub-mucosal dexamethasone injection had a significant beneficial postoperative effect on pain and trismus on the operating site [ 19 ], although there was no difference in late pain between the sub-mucosal, intravenous or intramuscular routes of administration [ 20 ]. Installation of a collagen sponge in the alveoli statistically significantly reduced pain [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%